Revitalizing community with traditional design: outlook platform, entrance archway, and bridge railings at KAED Malay heritage living lab - Mohamad Tajulddin Shah, Nur Aqilah Alia; Alias, Nur Ulfah Awatif Umairah; Tan, Chin Keng; Mohd Din, Azrin; Abdullah, Fadzidah; Azmin, Aida Kesuma (IIUM Press, 2024)
This project intends to enliven and give back the sense of belonging to community through a familiar setting of the local Malay traditional elements. The KAED Malay Living Heritage Lab is a part of public space in International Islamic University Malaysia (IIUM) that interlocks between active contexts including multiple faculties in IIUM, student hostel, external institutions and commercial spaces. In this project, public streetscape along the adjacent river, and a lookup point as a new structure to the site is proposed to benefit the community around the context to become an active "third place". The ultimate goal of this project is to propose a design of an outlook platform, an entrance archway and bridge railings at the KAED Malay Heritage Living Lab at IIUM. This project is in line with the second mission of IIUM which is to emphasize sustainable development in Malaysia and the Muslim world. After a site analysis and case study was conducted, adjacent to a restored "Rumah Kutai" that have been installed in the site in 2018, a design theme of "Nostalgia" was introduced in the design to evoke a sense of familiarity and belonging as a means to give back the public space to IIUM community. Within this design concept, the elements of public engagement, group gathering, cultivating knowledge of the traditional heritage and celebration of Islamic elements in a traditional build environment is applied. It gives a potential new breath to the site by celebrating elements of the past for the projection of the future with increased accessibility, functionality, and aesthetic appeal for the public community in IIUM.